The evolutionary and genetic origins of consciousness in the Cambrian Period over 500 million years ago - Feinberg, Todd E.; Mallatt, Jon (Frontiers in Psychology, 2013)
Vertebrates evolved in the Cambrian Period before 520 million years ago, but we do not know when or how consciousness arose in the history of the vertebrate brain. Here we propose multiple levels of isomorphic or somatotopic neural representations as an objective marker for sensory consciousness. All extant vertebrates have these, so we deduce that consciousness extends back to the group’s origin. The first conscious sense may have been vision. Then vision, coupled with additional sensory systems derived from ectodermal placodes and neural crest, transformed primitive reflexive systems into image forming brains that map and perceive the external world and the body’s interior. We posit that the minimum requirement for sensory consciousness and qualia is a brain including a forebrain (but not necessarily a developed cerebral cortex/pallium), midbrain and hindbrain. This brain must also have 1) hierarchical systems of intercommunicating, isomorphically organized, processing nuclei that extensively integrate the different senses into representations that emerge in upper levels of the neural hierarchy; and 2) a widespread reticular formation that integrates the sensory inputs and contributes to attention, awareness, and neural synchronization. We propose a two-step evolutionary history, in which the optic tectum was the original center of multi-sensory conscious perception (as in fish and amphibians: step 1), followed by a gradual shift of this center to the dorsal pallium or its cerebral cortex (in mammals, reptiles, birds: step 2). We address objections to the hypothesis and call for more studies of fish and amphibians. In our view, the lamprey has all the neural requisites and is likely the simplest extant vertebrate with sensory consciousness and qualia. Genes that pattern the proposed elements of consciousness (isomorphism, neural crest, placodes) have been identified in all vertebrates. Thus, consciousness is in the genes, some of which are already known.